Adoptive transfer of isolated bone marrow neutrophil - Tosello Boari, Jimena (2012)
Adoptive transfer experiments of specific cell populations are widely used methods to assess the role of the injected population on an ongoing process. In the last years, new and unprecedented roles in the regulation of immune responses have been reported for neutrophils. The following protocol is to be used to isolate neutrophils from bone marrow and to inject them in an appropriate host to test the role of neutrophils during infection, inflammation or other pathological conditions.